Transformacja ustrojowa a zjawisko globalizacji na przykładzie Polski - Rozmiarek, Mateusz (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The systemic transformation in Poland was part of globalization. Although this process has many positive virtues, Polish transformation was happening sort of besides the globalization, because it often didn’t include its crucial requirements and mechanisms. Poland didn’t work out a consistent, properly functioning model of economy. Systemic transformation of the economy enabled to reduce the civilization gap in relation to The West. On the other hand, it also caused a lot of problems. It led to ineffective privatization, monopolies in the economy and problems regarding a working institutional infrastructure in the country.